The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1093/ofid/ofz025
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Gut Virome Profile of Pregnant Women With Type 1 Diabetes in the ENDIA Study

Abstract: Background The importance of gut bacteria in human physiology, immune regulation, and disease pathogenesis is well established. In contrast, the composition and dynamics of the gut virome are largely unknown; particularly lacking are studies in pregnancy. We used comprehensive virome capture sequencing to characterize the gut virome of pregnant women with and without type 1 diabetes (T1D), longitudinally followed in the Environmental Determinants of Islet Autoimmunity study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 50 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…In our analysis of the longitudinal gut virome of 61 pregnant women (35 with type 1 diabetes and 26 without) in ENDIA, using VirCapSeq-VERT [22], 63% of samples tested positive for at least one virus and 29 genera of eukaryotic viruses were detected (Fig. 2).…”
Section: Virusesmentioning
confidence: 93%
“…In our analysis of the longitudinal gut virome of 61 pregnant women (35 with type 1 diabetes and 26 without) in ENDIA, using VirCapSeq-VERT [22], 63% of samples tested positive for at least one virus and 29 genera of eukaryotic viruses were detected (Fig. 2).…”
Section: Virusesmentioning
confidence: 93%
“…In organ transplant recipients, PBVs were predictive of the occurrence of severe enteric graft-vs.-host disease (GVHD), and correlated with the high levels of GVHD severity markers in feces (41). Recently, it was demonstrated that pregnant women with type 1 diabetes (T1D) are more likely to harbor PBVs than those without T1D (42).…”
Section: Picobirnavirus Infection In Humans and Animalsmentioning
confidence: 99%
“…The advent of metagenomics has greatly enhanced our ability to detect known and novel viral sequences in unbiased fashion and to establish novel associations of these sequences with various disease [1][2][3][4][5][6][7]. However, it is not known whether the virome plays a causative role or not.…”
Section: Lack Of Culture Systems To Propagate Components Of the Viromementioning
confidence: 99%